A comprehensive review on synthesis methods for transition-metal oxide nanostructures - Guo, Ting; Yao, Ming-Shui; Lin, Yuan-Hua; Nan, Ce-Wen (CrystEngComm, 2015)
Nanostructured transition-metal oxides exhibit excellent properties, such as ferromagnetic, ferroelectric, photoluminescence and semiconductive behaviors, etc. The band gap and electronic structure of these oxides can be controlled by size and dimensions; they can also be used in a wide range of applications including microelectronics, energy storage, sensors, and biomedicine due to their tunable chemical and physical properties. Here, we give a comprehensive review of the controllable growth of some typical transition-metal oxide nanostructures ( e.g. , WO x , FeO x , ZnO, TiO 2 , VO 2 , etc. ), which can be used to effectively understand the fabrication methods as well as the growth mechanism and inspire their potential applications. Recent developments of transition-metal oxide nanostructures with designed shape and dimensionality, including various synthesis methods and applications, are presented.